2017
DOI: 10.1186/s12936-017-2005-7
|View full text |Cite
|
Sign up to set email alerts
|

Malaria case management by community health workers in the Central African Republic from 2009–2014: overcoming challenges of access and instability due to conflict

Abstract: BackgroundIn the Central African Republic (CAR), decades of armed conflict have crippled the public health system. This has left the population without timely access to life-saving services and therefore vulnerable to the numerous consequences of infectious diseases, including malaria. As a response, in 2008 an international non-governmental organization started a network of community health workers (CHWs) in the highly malaria-endemic region of northwest CAR. The area has experienced years of violent clashes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 14 publications
0
32
0
1
Order By: Relevance
“…This is especially true in less-permissive environments, where high levels of mistrust are common and CHWs social standing can provide them with some level of protection. Indeed, CHW programs in the Central African Republic demonstrated that they could continue some level of care at all times, reach those most vulnerable populations, and maintain disease surveillance activities even in conflict zones (31).…”
Section: Future Opportunities: Recommendations For Engaging Communitymentioning
confidence: 99%
“…This is especially true in less-permissive environments, where high levels of mistrust are common and CHWs social standing can provide them with some level of protection. Indeed, CHW programs in the Central African Republic demonstrated that they could continue some level of care at all times, reach those most vulnerable populations, and maintain disease surveillance activities even in conflict zones (31).…”
Section: Future Opportunities: Recommendations For Engaging Communitymentioning
confidence: 99%
“…At a global level, studies show that in a mediumsized country, conflict can increase malnutrition by 3.3%, reduce life expectancy by 1 year, increase infant mortality by up to 10%, and cause other public health problems due to lack of access to drinking water, food and health services [7]. Although the epidemiological profile and burden of disease of countries in conflict has changed in the last decades, infectious diseases like malaria, tuberculosis, leishmaniasis, cholera, acute diarrheal disease and poliomyelitis, continue to be serious problems [8][9][10]. Conflict can also have devastating effects on sexual and reproductive health, neonatal health, mental disorders and noncommunicable diseases, such as cancer, hypertension and diabetes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite efforts to control malaria through multiple schemes coordinated by the National Malaria Control Program (NMCP), malaria continues to be the major public health problem according to the scientific literature and the CAR country profile in the World Malaria Report. In 2010, two studies showed prevalence rates of 65.8% and 64.9%, respectively, in children at the Bangui Pediatric Complex (CPB) and in pregnant women in the Ouham-Pendé Prefecture [8,9].…”
Section: Introductionmentioning
confidence: 99%